EFFECT OF BAKER’S YEAST (Saccharomyces cerevisiae) ON REARING OF Heterobranchus longifilis: GROWTH AND SURVIVAL IN OUTDOOR CONCRETE TANKS - OVIE , S. O; IBIYO, L. M. O; EZE, S. S. (Nigerian Journal of Fisheries, 2012)
Heterobranchus longifilis juveniles (117.68 ± 21.34 g) used for this study were product of an indoor experiment in glass aquaria transferred to outdoor tanks. This study is therefore, a continuation of the indoor study using the same feed for the fish outdoors for 230 days. They were stocked in ten concrete tanks, of sizes 2 m x 2 m x 1 m. The fish were stocked according to the number harvested from the indoor experiment for each treatment. The experimental diets were prepared with fish meal, soybean, groundnut cake, wheat offal, yeast, premix, starch, vitamin C and vitamin B-complex to meet the requirement of H. longifilis. The analysed crude protein in each diet is 42.56, 43.32, 43.69, 43.86 and 43.98. There was significant variation (P < 0.05) in the Mean Final Weight (MFW), Mean Weight Gain (MWG), Protein Efficiency Ratio (PER), Specific Growth Rate (SGR) and Percentage Survival (PS). The survival of the fish was highest with the fish fed 2 g yeast/100 g of diet and however this was not significantly different from fish fed 1g yeast/ 100g diet. The cost of production of one kilogram of fish using varying levels of S. cerevisiae in diets varied significantly (P < 0.05)